To secure the blessings of liberty : selected writings of Gouverneur Morris - Morris, Gouverneur, 1752-1816 (Liberty Fund, 2012)
Born into an aristocratic family in New York, Gouverneur Morris (1752-1816) completed his bachelor's degree at the age of sixteen from Columbia University (then King's College). He began reading law in the office of William Smith, one of the leaders of the New York bar. There he formed lifelong friendships with Robert Livingston and John Jay and earned a reputation as an expert in public finance through his opposition to a new issue of bills of credit by the New York colony. Morris's belief that human nature dictated self-serving goals in any political action made him a late convert to the cause of independence from Britain. Nevertheless, his optimism about the American future prevailed, and his political involvement during and after the American Revolution spanned more than three decades. As editor, J. Jackson Barlow writes, "Once he became an advocate of separation, Morris never looked back. By early 1776 he was taking a prominent part in revolutionary committees and had become a strong advocate of setting up an effective machinery of government." He served as Deputy Superintendent of Finance during the Revolution, in which capacity he devised a system of deminal coinage. As a New York delegate to the Continental Congress, Morris took his duties seriously. He visited Valley Forge and consulted closely with General George Washington on the needs of the army and the reforms needed to make it more effective. Morris came away with a lifelong admiration of Washington. As a prominent member of the Constitutional Convention, Morris wrote the final draft of the Constitution and authored the Preamble. Later, as a private citizen in Paris and minister to France (1789-94), Morris was a first-hand witness to the French Revolution and did what he could to protect Americans and French citizens alike from the worst ravages of the Reign of Terror. Upon his return to the United States, he served as a U.S. Senator, was a prime mover in the creation of the Erie Canal, and took a leading role as a critic of the Jefferson and Madison administrations. This collection of Morris's writings includes public letters, documents, and speeches, both published and unpublished, presented in chronological order. An introduction sets Morris's life and writings in the context of their time. Headnotes, a bibliography, and annotations offer further information. -- from dust jacket